FEATURES OF FACIAL WRINKLES AND EXPRESSION OF FACIAL EXPRESSIONS IN PORTRAITURE (American Journal of Research in Humanities and Social Sciences, 2025)
This article discusses the characteristics of facial wrinkles in portraiture, the importance given to human facial expressions by famous realist artists working in the field of portraiture and plot compositions, and their attempts to accurately and realistically express human inner feelings and emotions in portraiture.